Indigenous girls and the violence of settler colonial policing - Dhillon, Jaskiran K. (Decolonization: Indigeneity, Education & Society, 2015)
In cities and towns across Canada, Indigenous girls are being hunted, harassed, and criminalized by local law enforcement agents and the Royal Canadian Mounted Police. These normalized outbreaks of state control, often punctuated by the use of deadly force, are not isolated incidents in an otherwise just and fair social order. Rather, they are reflective of Indigenous girls’ daily realities embedded within the structure of an ongoing settler colonial social context that has strategically invented the criminal justice system to secure and maintain settler sovereignty. As such, this paper aims to redirect our critical analysis of the policing and caging of Indigenous girls through the geopolitics of settler colonialism. In the wake of mass protests against colonial state violence throughout 2014, resistance decrying the justice system and insisting that #BlackLivesMatters and that Indigenous lives matter, I argue that we have an urgent need to listen to the stories that Indigenous girls have to tell. These are not just any stories, but narratives that profoundly destabilize the hubristic portrayal of Canada as a humanitarian nation cleansed of settler colonial rule.
Number: 2
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; femmes* autochtones; femmes* et filles autochtones disparues et assassinées; féminisme décolonial; histoire et politique; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violences; violences d'état

La violence intersectionnelle dans la pensée féministe autochtone contemporaine - Perreault, Julie (Recherches féministes, 2015)
En parallèle avec les luttes des femmes sur le terrain, un courant théorique du féminisme autochtone se développe depuis la fin des années 90. Celui-ci revisite le narratif de la colonisation et la théorie postcoloniale en y intégrant l’analyse genre/« race ». L’auteure tente d’inscrire cette production intellectuelle au sein du paradigme intersectionnel universitaire et de la rendre accessible à un public francophone qui la connaît souvent moins bien. En replaçant la violence sexuelle et le patriarcat d’État au centre du débat, les féminismes autochtones arrivent à percevoir une dimension politique souvent laissée de côté par les analyses intersectionnelles.
http://www.recherchesfeministes.ulaval.ca
Keywords: approches et analyses; cours; discipline; fem1000; femmes* autochtones; féminisme décolonial; genre; identités LGBTQIA2+; intersectionnalité; pol4105; premier cycle; ressource en ligne; science politique; science politique et droit; sex2283; thématiques; violences